(untitled) (Boulder, Colo, 2005)
This exciting new book is about the narrative turn in sociology, an approach that views lived experience as constructed, at least in part, by the stories that people tell about it. The book is organized around four themes family and place, the body, education and work, and the passage of time that tell a story about the life course and touch on a wide range of enduring sociological topics. The first chapter explores some of the theories of narrative that mark contemporary social analysis. Introductions to the four sections identify the narrative style and sociological themes that the essays reflect. The heart of the book, however, is not about narrative but of narrative: scholars who have been involved in class, racial/ethnic, gender, sexual orientation, and disability studies compellingly write about their own life experiences
Keywords: Sociology,Narration (Rhetoric),Xã hội học; Methodology,Phương pháp nghiên cứu